URGENCY OF REGULATION REFORM OF BRIBERY OFFENCE AT PRIVATE SECTOR IN INDONESIA - Nabila Ayu Umari; Diana Lukitasari; Ismunarno Ismunarno (IJCLS (Indonesian Journal of Criminal Law Studies), 2019)
This research aims to assess the urgency of regulation reform of bribery offence at private sector in Indonesia. This study used doctrinal research methods with prescriptive characteristic. The approach used is legal approach. The legal substances used in this study are primary and secondary legal materials. The techniques of collecting legal materials are by library research and analysis techniques of legal materials using deduction methods. The results showed that the arrangement of bribery in private sector offences in Indonesia still has various problems with the unenactment of Law Number 11 of 1980 on Bribery Offences effectively and impressed forgotten. KPK has attempted to revise the Corruption Act through the Corruption Criminal Act Draft which included articles relating to bribery in private sector offences by adopting the provisions of Article 21 UNCAC. However, the Corruption Criminal Act Draft still lacked a shortage of passive bribery offences.